TINGKAT PENGETAHUAN KELUARGA DALAM PEMBERIAN GIZI PADA LANSIA CEPOGO, BOYOLALI - Isnani Nurhayati; Tri Yuniarti; Anggie Pradana Putri (JURNAL RISET GIZI, 2019)
Background : Nutrition is one of the important factors in achieving health status. Indonesia is currently experiencing an increase in life expectancy and an increase in the number of elderly people. Therefore, elderly health needs to get special attention in giving nutrition. The importance of the role of families with the elderly, one of which is nutrition. Objective : to find out the relationship between the level of family knowledge in providing nutritious food to the elderly with nutritional status of the elderly. Methods : This research is analytical descriptive with cross sectional approach. The population is all families who live with the elderly, taking samples with purposive random sampling, obtained 43 respondents. The instrument uses questionnaires containing knowledge of nutrition and anthropometry to determine nutritional status. Univariate and bivariate data analysis with Chi Square test. Results : Of the 43 families with the elderly, the junior high school education level was 42%, the level of family knowledge in providing nutrition to the elderly with knowledge of the turtle was 46% and the nutritional status of the elderly was 42% obese. Based on the results of the Chi Square statistic test, the p value of 0.003 0.05 means that there is a significant relationship between the level of family knowledge in providing nutrition for the elderly and nutritional status. The higher the level of knowledge of the family, the better the nutritional status.Conclusion : There is a significant relationship between family knowledge about providing nutrition with the nutritional status of the elderly.